Społeczno-obyczajowe uwarunkowania porzucania dzieci i dzieciobójstwa w Królestwie Polskim na przełomie XIX i XX wieku - Bołdyrew, Aneta (Biuletyn Historii Wychowania, 2012)
In the last decades of the 19th century, in the Kingdom of Poland, the scale of social pathologies increased, including infanticide and abandonment of children. Such phenomena were conditioned by a number of social, demographic, economic and moral factors; the processes of urbanization and industrialization played a major part as they resulted in the inflow of great masses of people to cities, who experienced difficulties in the adaptation to new conditions. Poverty, illiteracy, often the lack of steady employment, disintegration of the traditional social groups and the system of values lead to the destabilization of the situation of the immigratory population. This made starting a family difficult, leading to a large number of informal relationships, lone mothers and illegitimate children deprecated by public opinion. The hardships of lonely maternity, lack of support on the part of the state administration and shelters determined the increased number of crimes against children. Also, unfavourable was a common practice of employing wet nurses, who left their own children in the care of hired babysitters, who were knowingly called the “producers of angels” because of the fact of a huge mortality rate among such infants, dying as a result of disastrous care, or, sometimes, simply murdered. Social work of pedagogues, doctors and lawyers slightly improved the fate of the poorest mothers, who most often committed infanticide and abandonment of their children, and, consequently, the scale of such phenomena at the beginning of the 20th century slightly decreased.